Infrared spectra of soil organic matter under a primary vegetation sequence - Nuzzo, A.; Buurman, P.; Cozzolino, V.; Spaccini, R.; Piccolo, A. (Chemical and Biological Technologies in Agriculture, 2020)
Abstract Background We applied Fourier-Transformed Infrared Spectroscopy (FTIR) techniques in combination with selective humus extractions to investigate in situ the chemical features of organic matter in three soil profiles recently developed from Dutch sand dunes, under well-documented vegetation sequence and containing a relatively simple mineral-organic matter system. Water-soluble and alkaline-soluble extracts were also studied to match the changes of humus in the soil residues. Results Diffuse Reflectance Infrared Fourier Transform (DRIFT) and transmission spectra differed in resolution and sensitivity. DRIFT was superior in revealing structural information on the organic matter present in the soil samples whereas transmission spectra showed higher resolution for the bands of inorganic material at lower spectral frequencies. Differences between H and B horizons were due to the amount of hydrophilic organic acids, partly unsaturated, that were extracted by alkali. Extractable carboxylic acids and other hydrophilic compounds such as peptides and carbohydrates were larger in the less developed soils under pine and crowberry than in the more advanced profiles under beech. Humin residues from both H and B horizons retained unextractable aliphatic components and carboxylic groups involved in strong complexes with minerals, thereby confirming other findings that showed the largely aliphatic character of the unextractable humic fraction. Accumulation of poorly-soluble organic materials in these soils occur by protection from biodegradation due both to complexation with soil minerals and to a process by which apolar humic constituents form a separate hydrophobic phase where no biological activity can take place. Transport of poorly soluble compounds from H to B horizons, noticed especially in the more developed profiles, may have occurred through humic aggregates containing hydrophobic phases. Conclusions This work shows that the DRIFT technique in combination with soil chemical treatments can be suitably employed ...